2021
DOI: 10.1111/jrh.12581
|View full text |Cite
|
Sign up to set email alerts
|

Rural‐urban differences in informal caregiving and health‐related quality of life

Abstract: Objectives Rural‐urban health disparities are pervasive among older adults. Rural US locations have a disproportionately high population of older adults, have reduced access to services, and are therefore more reliant on family and friends for care. However, little is known about rural‐urban disparities among the 40+ million informal caregivers nationwide. There is a critical need to understand how rural‐urban disparities impact caregiving experiences and health‐related quality of life (HRQoL). The objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Besides the well-known influence of these variables on HRQoL and physical health status in older people, there is some evidence that older rural residents experience a health disadvantage compared to urban residents [ 34 ]. Nonetheless, there is no consistent evidence that older people living in rural areas have low scores of physical fitness, PA, and HRQoL compared to those living in urban areas [ 35 , 36 , 37 , 38 ]. For instance, in studies performed in China ( n = 1029) and Brazil ( n = 2292), the urban older residents showed greater HRQoL than their rural counterparts [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the well-known influence of these variables on HRQoL and physical health status in older people, there is some evidence that older rural residents experience a health disadvantage compared to urban residents [ 34 ]. Nonetheless, there is no consistent evidence that older people living in rural areas have low scores of physical fitness, PA, and HRQoL compared to those living in urban areas [ 35 , 36 , 37 , 38 ]. For instance, in studies performed in China ( n = 1029) and Brazil ( n = 2292), the urban older residents showed greater HRQoL than their rural counterparts [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may be particularly helpful among rural caregivers, who are known to experience more caregiver burden and strain than their urban counterparts. 13,18 Additionally, a Canadian study of older adults found that those receiving both family and paid care reported greater autonomy and social connectedness, and a reduced sense of being a burden on their family members, than those without shared care. 23 These studies suggest that shared care may be beneficial for caregivers and care recipients alike.…”
Section: Discussionmentioning
confidence: 99%
“…7,15 Prior studies have also shown that family caregiving is more prevalent in rural areas compared to urban ones and that rural family caregivers experience higher levels of caregiver strain compared to their urban counterparts. 13,[16][17][18] This suggests that rural family caregivers, as well as those in certain geographic regions, may benefit from sharing the care of their loved ones with paid caregivers; however, the extent to which they do so is currently unknown. That is, despite its rising prevalence, less is known about patterns of shared caregiving, and whether differences exist by rurality and region in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of informal caregivers will likely grow due to the increasing prevalence of chronic diseases and population aging ( Reinhard et al, 2019 ). Research conducted in the United States has found that informal caregivers are more likely to report fair or poor health status and more days of poor physical and mental health than non-caregivers ( ​Cohen, et al, 2021​ ). Research also suggests that caregiver burden may negatively impact caregivers’ ability to engage in healthy behaviors ( Mochari-Greenberger & Mosca, 2012 ) and increase caregiver risk of poor health and chronic diseases ( Miyawaki et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%